Insights into Ultrasound-Assisted Postharvest Preservation: Metabolic, Structural, and Quality Changes in Strawberries During Storage - Yildiz, Gokcen; Yildiz, Gulcin (Springer, 2025)
This study investigates the effects of high-intensity ultrasound (HIU), chemical treatment (ascorbic acid and calcium chloride), and physical treatment (water bath at 65 degrees C) on the metabolic and structural changes in strawberries during 14 days of storage. Ultrasound applications demonstrated potential in preserving freshness, enhancing nutrient retention, inhibiting microbial growth, and minimizing enzymatic browning in fresh produce. Treated strawberry samples were stored at 4 degrees C, with analyses conducted on days 1, 3, 7, and 14 to assess antioxidant capacity (DPPH, FRAP, ORAC), total phenolic content, total flavonoid content, ascorbic acid content, enzyme activities (polyphenol oxidase [PPO] and pectin methyl esterase [PME]), texture, color, microbial load, and sensory attributes. Ultrasound treatment significantly (p < 0.05) inhibited microbial growth (bacteria, mold, and yeast), improved bioactive compound retention, reduced enzymatic activities, and minimized browning compared to other treatments. Ultrasound-treated samples also maintained superior color parameters, exhibited lower decay rates, and had better sensory scores, particularly regarding off-odor. By extending shelf life, reducing enzymatic degradation, and preserving nutritional and sensory qualities, this study highlights ultrasound as a promising scalable, non-thermal approach for the postharvest preservation of strawberries and fresh-cut produce, aligning with the demand for clean-label, minimally processed foods.
Keywords: High-intensity ultrasound; Antioxidant capacity; Enzymatic browning; Strawberry; Metabolic changes